(untitled) (Journal of Educational Sciences, 2016)
The author analyzes the transformation of the Kazakh national ideas in the Kazakh state national idea. At the present stage of development of domestic pedagogical science of searching for a new system of values and resolve the contradictions in public consciousness – Kazakhstan national idea. Then the author gives the data of the latest achievements, current situation, the new features of the system of education of the Republic. The structure of highereducation is aligned with the International standard classification of education, restructured technical and vocational education, created a national system of education quality assessment, incorporating elements of an independent external evaluation, the conditions for the introduction of 12-year education model. Overseas trained more than 20 thousand people of Kazakhstan, about 3000 international scholarship of the President of the Republic of Kazakhstan «Bolashak» study in 27 countries. At the same time, States the problem of necessity of improvement of quality of education in Kazakhstan. The main idea of the article is the thesis of expansion and strengthening ethnic-pedagogical and multicultural components as the basis of Kazakhstan’s education. Moreover ethnic-pedagogical and multi-ethnic approach should be non-fragmentary, and global, comprehensive, systematic nature of modern teaching and upbringing. The article considers the history-graphical research data multi-ethnic culture. Demonstrated problem of formation of the multiethnic culture student at the modern stage of development of pedagogical science. See historiography of Kazakhstan scientists in the field of research a multi-ethnic culture in the context of post-Soviet scientific works and interdisciplinary vision. Discusses the idea of a multicultural environment education of the young generations of Kazakhstani people. It is established that the science has been the development of individual scientific schools (ethnic-pedagogical, ethnic- psychological, pedagogical of humanism and others), studying various aspects of inter-ethnic relations, the value orientation of the younger generation, personality schoolchildren, providing productive-creative transformation of multi-ethnic environment as part of a multi-ethnic culture.